Psychological distress and coping strategies among the caretakers of children with transfusion-dependent thalassemia - Othman, Azizah; Abdul Ghani, Mohd Sufian Ardi; Taib, Fahisham; Mohamad, Norsarwany (Frontiers in Pediatrics, 2022)
Introduction: Thalassaemia is a chronic childhood disease which could result in psychological distress not only to the patients but also their caretakers. Caretakers utilize different coping strategies to reduce the stress and to maintain good quality of life. Objective: The study aims to measure the level of psychological distress among caretakers of transfusion dependent thalassaemia patients and to identify coping strategies used by them, as well as to examine factors related to both outcome measures. Methods: Sixty-eight (N=68) caretakers of children with transfusion dependent thalassemia agreed to participate in the study when they were approached during their visits at one of three major hospitals in Kelantan, Malaysia for the children’s medical treatment. They completed the Malay validated Depression Anxiety and Stress Scale 21 (DASS 21) and brief COPE self-report, in addition to a brief study proforma. Results: Majority of the participants reported feeling psychologically well, with no elated scores in depression, anxiety, and stress sub-scales. The mean score for anxiety and stress sub-scales were 3.54 (SD=3.54) and 4.25 (SD=3.26) respectively. The median score for depression sub-scale was 2.00 (IQR 4.00). Three mostly utilized coping strategies were religion, acceptance and positive reframing. Those with depressed and anxious mood were found to engage more in negative coping strategies including use of substance, denial and behavioral disengagement. Being female, of younger age, employed, with higher educational level and income status were found to significantly predicted more use of positive reframing as coping strategy. Conclusion: Psychological distress such as elevated anxiety and depressed mood was found among small portion of caretakers who have children with thalassemia whose treatment required blood transfusion. They were noted to apply more maladaptive coping strategies compared to psychologically well counterparts.